2019
DOI: 10.1038/s41593-018-0293-z
|View full text |Cite
|
Sign up to set email alerts
|

Premature polyadenylation-mediated loss of stathmin-2 is a hallmark of TDP-43-dependent neurodegeneration

Abstract: Amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) are associated with loss of nuclear TDP-43. Here we identify that TDP-43 regulates expression of the neuronal growth-associated factor stathmin-2. Lowered TDP-43 levels, which reduce its binding to sites within the first intron of stathmin-2 pre-mRNA, uncover a cryptic polyadenylation site whose utilization produces a truncated, non-functional mRNA. Reduced stathmin-2 expression is found in neurons trans-differentiated from patient fibroblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
522
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 435 publications
(619 citation statements)
references
References 57 publications
30
522
0
Order By: Relevance
“…Similarly, examination of downregulated genes overlapping among the Blue and Midnightblue modules in data set A, the Darkgreen module in data set B, and MNs highlighted genes previously implicated in ALS (Lederer et al, 2007;Saris et al, 2009;Umahara et al, 2016) ( Figure 5D). The GO term regulation of neuronal projection development was significantly represented among the overlapping, downregulated genes ( Figure 5D), consistent with recent models suggesting that deficiencies in maintaining axonal projections may underlie ALS (Klim et al, 2019;Melamed et al, 2019).…”
Section: Als Ipsc-mn Cultures Exhibit Transcriptional Changes Detectasupporting
confidence: 88%
See 2 more Smart Citations
“…Similarly, examination of downregulated genes overlapping among the Blue and Midnightblue modules in data set A, the Darkgreen module in data set B, and MNs highlighted genes previously implicated in ALS (Lederer et al, 2007;Saris et al, 2009;Umahara et al, 2016) ( Figure 5D). The GO term regulation of neuronal projection development was significantly represented among the overlapping, downregulated genes ( Figure 5D), consistent with recent models suggesting that deficiencies in maintaining axonal projections may underlie ALS (Klim et al, 2019;Melamed et al, 2019).…”
Section: Als Ipsc-mn Cultures Exhibit Transcriptional Changes Detectasupporting
confidence: 88%
“…The most recent iPSC-based transcriptomic reports performed RNA profiling at time points during differentiation concomitant with various observed ALS phenotypes which include nuclear RNA foci (Sareen et al, 2013), decreased neurite length (Fujimori et al, 2018), reduced neurite repair after injury (Klim et al, 2019;Melamed et al, 2019), and MN death (Kiskinis et al, 2014;Shi et al, 2018). Several of these protocols differentiated iPSCs for over 30 days, and many required a relatively prolonged maturation phase, the presence of glia, and additional stressor conditions in order to yield a disease phenotype.…”
Section: Single-cell Analysis Enables Attribution Of Early and Convermentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported that TDP-43 naturally de-mixes in the nucleus, and shuttles to the cytoplasm in response to multiple stresses (21). Loss of nuclear TDP-43 causes usage of cryptic splice (22)(23)(24) and polyadenylation sites (24), dysregulating many important neuronal genes such as HDAC6 (25) and stathmin-2 (22,24).…”
Section: Mislocalization and Aggregation Of The Heterogeneous Nuclearmentioning
confidence: 99%
“…TDP-43 can associate with more than 6,000 RNA targets 4144 , and RNA-binding is antagonistic to toxic TDP-43 oligomerization in an optogenetic cellular model 28 , implying that light-dependent opTDP-43 oligomerization would profoundly affect its RNA-binding capacity, thereby influencing the expression of a myriad of genes. In terms of the axon outgrowth defect, whether toxicity is ascribable to dysregulation of specific key proteins 39, 45 or to a widespread translational abnormality 46 , which could lead to stress-inducing misfolded protein accumulation, remains to be investigated. Nevertheless, the normal motor axon pathfinding and unaffected branching frequency suggest a certain specificity of opTDP-43 toxicity and would favor the idea that the cellular growth pathway is primarily affected by the toxicity.…”
Section: Discussionmentioning
confidence: 99%